2020
DOI: 10.1259/bjr.20200819
|View full text |Cite
|
Sign up to set email alerts
|

Prostate cancer measurements on serial MRI during active surveillance: it’s time to be PRECISE

Abstract: Objective: The PRECISE criteria for reporting multiparametric MRI in patients on active surveillance (AS) for prostate cancer (PCa) score the likelihood of clinically significant change over time using a 1–5 scale, where 4 or 5 indicates radiological progression. According to the PRECISE recommendations, the index lesion size can be reported using different definitions of volume (planimetry or ellipsoid formula) or by measuring one or two diameters. We compared different measurements using planimetry as the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 24 publications
2
7
0
Order By: Relevance
“…Here, we show that all three T 2 WI-derived tumour measurements demonstrated comparable diagnostic performance for predicting histopathological progression on AS, consistent with a previous study by Giganti et al 20 Clinically, evaluating serial changes in maximum tumour diameter closely mirrors the RECIST 1.1 criteria 30 used in oncology to assess treatment outcomes. In our study, the median relative change in T 2 WI-derived maximum tumour diameter in progressors was 21.7%, which corresponded to the doubling of the median tumour volume in this group.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Here, we show that all three T 2 WI-derived tumour measurements demonstrated comparable diagnostic performance for predicting histopathological progression on AS, consistent with a previous study by Giganti et al 20 Clinically, evaluating serial changes in maximum tumour diameter closely mirrors the RECIST 1.1 criteria 30 used in oncology to assess treatment outcomes. In our study, the median relative change in T 2 WI-derived maximum tumour diameter in progressors was 21.7%, which corresponded to the doubling of the median tumour volume in this group.…”
Section: Discussionsupporting
confidence: 89%
“…Using these cut-offs to supplement subjective serial MRI assessment could help improve the quality of MRI-guided AS programmes and further reduce the need for unnecessary biopsies while increasing the positive predictive value for histopathological disease progression. A previous study has shown similar relative increase in T 2 WI-derived maximum tumour diameter in AS patients with radiological disease progression, 20 which is expected since the increase in size is an integral feature of PRECISE categories 4–5. 24 In addition, our findings are consistent with the annual increases in tumour volumes (up to 23%) and diameters (up to 7%) reported by Giganti et al 31 on different magnets using different scanning protocols, which supports the potential clinical applicability and reproducibility of our results.…”
Section: Discussionsupporting
confidence: 65%
“…We observe that PSAD change prompts further assessments through imaging or biopsy and is, therefore, associated with outcome. Future research should expand on these considerations and explore the potential of multivariable models with additional longitudinal predictors beyond PSAD [9,10]. There was a steady increase in mean prostate volume over time (spline curve shown), at an approximate average rate of 3.3 mL/ year.…”
Section: Discussionmentioning
confidence: 99%
“…15 Prostate volume can be calculated even more accurately when planimetry is applied. 16 Furthermore, a new technique (Biproximate) was proposed which uses more precise and reproducible reference points as an alternative to measuring the ellipsoid volume. 17 Given that PSA density is a function of volume, PSA density is therefore not obtained with precision, and may vary depending on which method or technique is used.…”
Section: E D I T O R I a Lmentioning
confidence: 99%
“…The midaxial plane is recommended for this measurement in PI‐RADS v2, while the midsagittal plane is recommended in PI‐RADS v2.1 15 . Prostate volume can be calculated even more accurately when planimetry is applied 16 . Furthermore, a new technique (Biproximate) was proposed which uses more precise and reproducible reference points as an alternative to measuring the ellipsoid volume 17 .…”
mentioning
confidence: 99%